Intra-family Violence (IFV): A brief review - Tofenio Moreyra, Nancy Marlene (2019)
The purpose of the present research work is to conduct a bibliographic search about intrafamily violence, trying to have a closer look that allows us understand this scourge that currently affects society, due to the violence has become a form of interrelation between family members. A review of different authors from different countries will be conducted, since this fact is a common feature within many families that become dangerous places for the most vulnerable members, which historically are children and women. In addition, the consequences of abuse at a physical, psychological and neurological level will be reviewed.